Modelling survival and growth prediction of Swietenia macrophylla king (mahogany) plantation at Kolapis, Sabah. - Abd. Kudus, Kamziah; Zainor, Zulfadhli; Chia, Fui Ree; Lapongan, Jaffirin; Pang, K. N. K. (Forest Research Institute Malaysia, 2011)
This study was carried out to determine the appropriate growth model for Swietenia macrophylla plantation at Luang Manis, Kolapis, Sabah. It included exploratory data analysis, development of survival and growth prediction models, basal area estimation and model comparison to determine the most appropriate model to predict the optimum age for harvesting. The growth prediction models were evaluated using Proc Reg and Proc Nlin in SAS and Kaplan Meier estimation was adapted for survival estimation. The models were compared on the basis of bias, root mean square error (RMSE) and coefficient of determination (R2). The results were supported by the findings from the basal area prediction. Results showed that the most suitable diameter prediction models were; lnD̂=3.49-(5.45/A) with RMSE (0.40), bias (1.43) and R2 (0.56) and lnD̂=0.97+0.73 lnA with RMSE (0.40), bias (1.45) and R2 (0.55). While the recommended height prediction model was lnĤ=1.00+0.12D-0.0016D2 with RMSE (0.22), bias (-2.01) and R2 (0.86). The growth prediction models recommended that the optimum age that give maximum yield per hectare is at 25 years.